Structural regulation of ZnGa2O4 nanocubes for achieving high capacity and stable rate capability as an anode material of lithium ion batteries. (1st May 2017) - Han, Nao; Chen, Dairong; Pang, Yingping; Han, Zhiming; Xia, Yuguo; Jiao, Xiuling
Abstract: Increasing demand for high energy capability Li rechargeable batteries has promoted extensive research on the development of electrode materials. Multi-component spinel metal-oxide is considered to be promising anode material owing to their better electrical conductivity and higher electrochemical activity. Herein, a facile one-pot strategy without further thermal annealing treatment is successfully developed for preparation of well-defined ZnGa2 O4 nanocubes. To the best of our knowledge, this is the first report on the synthesis of ZnGa2 O4 nanocubes through wet chemical method and applied as anode material. Galvanostatic charge and discharge results indicate ZnGa2 O4 nanocubes electrode is capable of delivering a higher capacity and better cycling stability than ZnO/Ga2 O3 mixture electrode. Noteworthily, ZnGa2 O4 nanocubes electrode also exhibites superior capacity compared with ZnGa2 O4 nanospheres electrode which is consisted of secondary nanoparticles. Large amount of ZnGa2 O4 nanocubes could retain their morphology after 160 charge/discharge cycles and further surface elemental analysis illustrates elements distributions has no changes in the surface. The unique structure and high crystallinity is responsible for higher capacity and better cycling stability.